EyeNav: a novel accessibility-driven system for interaction and automated test generation using eyetracking and natural language processing (2025)
EyeNav is a novel system that combines eye tracking and natural language processing (NLP) to enhance accessibility and enable automated test generation. This research demonstrates the integration of these technologies for intuitive web interaction, enabling pointer control via gaze and natural language processing for interpreting user intentions. Additionally, it presents a record-and-replay module for generating automated test scripts. Preliminary user evaluations yielded positive results in terms of usability. The ultimate goal is to demonstrate that eye tracking combined with NLP can be effectively used not only as a possible assistive technology but also as an innovative approach to software testing.